PERANAN DAN KEDUDUKAN TENTARA NASIONAL INDONESIA (TNI) DI DALAM RANCANGAN UNDANG-UNDANG KEAMANAN 102 NASIONAL DI TINJAU DARI PERSPEKTIF POLITIK HUKUM DI INDONESIA - Munsharif Abdul Chalim; Faisal Farhan (UNISSULA, 2015)
The formation of the armed forces in modern States intended to protect and defend the sovereignty of the State and the Nation State. But in reality, there are some inherent in expanding the role of the armed forces. The research method using normative juridical approach with The data collection methods focus on literature study materials secondary law. The results obtained are 1) The nature of national security are all efforts quickly, gradual and integrated by empowering all national forces to create security and stability through a system of national security, national security objectives, aims to create a safe condition of the nation and the Unitary State of the Republic of Indonesia physically and psychic each individual citizen, the people, the government and the State, in order to protect national interests, and delivery functions of national security is to: Establish, maintain, and develop a system of national security as a comprehensive, integrated, focused and realize all areasof national jurisdiction as a unified national security. 2) Politics of law contained in the preparation of a draft law of national security The main objective is to realize a safe condition of the nation and the State unitary Republic of Indonesia physically and psychologically every individual citizen, the people, the government and the State, in order to protect national interests.